The long-term clinical course of moderate tricuspid regurgitation. (3rd October 2022) - Margonato, D; Ancona, F; Melillo, F; Ingallina, G; Stella, S; Biondi, F; Manini, C; Montorfano, M; Maisano, F; Topilsky, Y; Agricola, E
Abstract: Background: Moderate TR is a frequent condition, worsening mid and long-term survival, particularly in patients >75 years old, and in those suffering from left ventricular systolic dysfunction. As TR is often clinically unsuspected until an advanced stage of congestive heart failure (HF), there is a great need of early diagnosis and long-term appropriate follow-up. However, data focusing on the clinical and echocardiographic course of a cohort of patients with moderate TR is lacking, and the most appropriate type and time of management of these patients is still heavily debated. Purpose: To evaluate the evolution and the long-term clinical outcome of a cohort of patients suffering from moderate and moderate to severe TR, regardless of its etiology. Methods: Clinical outcome and echocardiographic follow-up were assessed in 212 patients diagnosed with moderate and moderate to severe TR in our centre between January 2014 and December 2019. TR progression at follow-up was defined as TR grade increase to at least severe. The primary endpoint was all-cause death; secondary endpoints were cardiovascular (CV) death and HF hospitalization. Results: After a median follow-up of 4.2 years, TR progression occurred in 76 patients (36%): patients with TR progression presented with more history of coronary artery disease (p=0.042), atrial fibrillation (AF, p=0.007) and chronic kidney disease (CKD, p=0.007) and with baseline larger right ventricle end-diastolic diameter (RVEDD, p<0.001) and worse left ventricular ejection fraction (LVEF, p=0.048). After univariate and multivariate analyses, a history of AF (HR 2.3, CI 1.2–4.5, p=0.011) and RVEDD (HR 2.4, CI 1.3–4.4, p=0.003) were independent predictors of TR progression. The primary endpoint occurred in 57 patients (27%) and was significantly more frequent (p=0.015) in the group of patients with TR progression compared to those without TR progression; multivariate analyses showed TR grade progression (HR 4.3, CI 2.1–9.1, p<0.001), CKD (HR 3.2, CI 1.5–7.1, p=0.002) and LVEF (HR 0.9, CI 0.93–0.99, p=0.007) as being independently associated with the primary outcome. Moreover, both CV death (p=0.003) and HF hospitalization (p=0.0139) were significantly more frequent in patients with TR progression. Conclusions: Our results showed that moderate TR, by progressing in a relevant proportion of patients over a long-term follow-up, significantly increases the risk of mortality and HF hospitalization. We identified specific risk factors associated with TR progression, which could help to identify patients at risk before an advanced stage of this disease. We believe that this cohort of patients should be appropriately managed and closely followed-up to avoid adverse clinical events related to the natural course of this valvulopathy. Funding Acknowledgement: Type of funding sources: None.